Multielement Characterization and Antioxidant Activity of Italian Extra-Virgin Olive Oils - Astolfi, Maria Luisa; Marini, Federico; Frezzini, Maria Agostina; Massimi, Lorenzo; Capriotti, Anna Laura; Montone, Carmela Maria; Canepari, Silvia (Frontiers in Chemistry, 2021)
Food product safety and quality are closely related to the elemental composition of food. This study combined multi-element analysis and chemometric tools to characterize 237 extra-virgin olive oil (EVOO) samples from 15 regions of Italy, and to verify the possibility of discriminating them according to different quality factors, such as varietal or geographical origin or whether organically or traditionally produced. In particular, the antioxidant activity of oils’ hydrophilic fraction was estimated and the concentrations of 45 elements were determined by inductively coupled plasma mass spectrometry (ICP-MS). At first, univariate and multivariate analysis of variance were used to compare the element concentrations, and statistically significant differences were found among samples from different regions. Successively, discriminant classification approaches were used to build a model for extra-virgin olive oil authentication, considering, in turn, various possible categorizations. The results have indicated that chemometric methods coupled with ICP-MS have the potential to discriminate and characterize the different types of EVOO, and to provide “typical” elemental fingerprints of the various categories of samples.